2012
DOI: 10.1111/j.1365-2966.2012.21873.x
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental parameters and infrared excesses ofHipparcosstars

Abstract: We derive the fundamental parameters (temperature and luminosity) of 107 619 Hipparcos stars and place these stars on a true Hertzsprung–Russell diagram. This is achieved by comparing bt‐settl model atmospheres to spectral energy distributions (SEDs) created from Hipparcos, Tycho, Sloan Digital Sky Survey, DENIS, Two Micron All Sky Survey, MSX, AKARI, IRAS and Wide‐field Infrared Survey Explorer data. We also identify and quantify from these SEDs any infrared excesses attributable to circumstellar matter. We c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
244
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(277 citation statements)
references
References 58 publications
29
244
3
1
Order By: Relevance
“…van Leeuwen (2007) reported a Hipparcos parallax of 20.31 mas, placing it at a distance of r ≈ 49 pc. McDonald et al (2012) reported an effective temperature of T eff ≈ 6032 K, while the estimate of Vican & Schneider (2014) was T eff ≈ 6100 K. Furthermore, Vican & Schneider (2014) reported a radius of R ≈ 1.05 R , while Zuckerman et al (2011) presented the value R ≈ 1.08 R . We adopted the value 1.1 R .…”
Section: V1358 Orimentioning
confidence: 99%
“…van Leeuwen (2007) reported a Hipparcos parallax of 20.31 mas, placing it at a distance of r ≈ 49 pc. McDonald et al (2012) reported an effective temperature of T eff ≈ 6032 K, while the estimate of Vican & Schneider (2014) was T eff ≈ 6100 K. Furthermore, Vican & Schneider (2014) reported a radius of R ≈ 1.05 R , while Zuckerman et al (2011) presented the value R ≈ 1.08 R . We adopted the value 1.1 R .…”
Section: V1358 Orimentioning
confidence: 99%
“…Silicates are also expected to produce spectral features in the 8-14 µm range, unless the grains are extremely large. Amorphous carbon, on the other hand, can produce a featureless mid-infrared continuum (McDonald et al 2012). Amorphous carbon has also been favored in the cases of other dust producing WRs (Williams et al 1987), and so it might be the most plausible dust chemistry for NaSt1.…”
Section: Dust Formation From Colliding Winds?mentioning
confidence: 99%
“…We first approximate the spectrum of the PSF reference star with a template spectrum with the corresponding effective temperature and the luminosity class available in the spectral library of Pickles (1998). Based on the effective temperature of 4548 K estimated for HIP67834 (McDonald et al 2012), we adopted the spectrum of a K2III star in the spectral library of Pickles (1998), whose effective temperature is the closest to HIP67834. We reddended the spectrum with A V = 0.24, which was obtained using the parameterization of the interstellar extinction of Arenou et al (1992) and the wavelength-dependence of the interstellar extinction derived by Cardelli et al (1989).…”
Section: Visible Polarimetric Imaging Observations With Sphere-zimpolmentioning
confidence: 99%